(untitled) (Revista Argentina de Musicología, 2020)
This article reflects about the social functions of Lima’s independent music festivals. I propose to understand them as a complex system of artistic production organizations that generate liminal ritual events where cultural inputs associated with the cosmopolitan Peruvian identity that participate in tense disputes in the construction of the public scene are discovered, negotiated, affirmed and reinvented. I will trace the historical trajectory of the rock festivals and the presence of “rock fusion”, to identify the festivals that led the independent music market before the pandemic, organized by Selvámonos, Inmortal, Descabellado and the Municipality of San Isidro. I will show their ways of articulation and organization. Then I will stop to analyze a guitar ornament of La Mente, Barrio Calavera and Olaya Sound System, protagonists of festivals, which incorporate features of chicha, relocating the prestigious position of Peruvian musical elements in public opinion. In parallel, I will observe how the Do It Yourself/Together dynamics of independent festivals affect the management of public festivals. Thus, I will show how festivals participate in the reproduction of society by their ability to define which are the available cultural inputs and the sustainable musical circuits.